Building a school reading culture: Teacher librarians' perceptions of enabling and constraining factors. Issue 2 (August 2019) - Merga, Margaret Kristin; Mason, Shannon
A supportive school reading culture is an educative context in which there is availability, opportunity, encouragement and support for reading. Little is known about whether Australian schools actively foster reading cultures that are supportive of reading for pleasure. In their role as reading advocates, teacher librarians may be uniquely situated to provide valuable insights into the factors that enable and constrain the development of a whole school reading culture. Interview data from teacher librarians at 30 Western Australian schools were drawn upon to explore the factors and characteristics that are believed to both enhance and limit school reading cultures. Our research suggests that school leadership may play a crucial role in the development and maintenance of a school reading culture that positions reading as both valuable and pleasurable. More broadly, a school reading culture is supported by numerous additional factors that may be influenced by, but not wholly determined by leadership support.